Differences in Knowledge of Sexually Transmitted Infections Before and After Video-Based Education Among Premarital Couples - Zahra Diva Ananda; Mega Octamelia; Andi Sri Hastuti Handayani Usman; Nurul Hidayatun Jalilah; Eka Darmayanti Putri Siregar (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2026)
One of the government’s efforts to prevent the transmission of sexually transmitted infections among premarital couples is the requirement to undergo screening at community health centers and attend premarital counseling at the Office of Religious Affairs before obtaining a marriage schedule. This study aimed to determine the effect of video-based educational media on the knowledge of premarital couples regarding sexually transmitted infections. This quantitative study used a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 38 premarital couples selected through accidental sampling. Data were collected using a validated and reliable questionnaire on knowledge of sexually transmitted infections. Data analysis was conducted using univariate analysis and bivariate analysis with the Wilcoxon test. The results showed an increase in the mean knowledge score of 14.74 after the intervention, indicating a significant effect of video-based education on the knowledge of premarital couples (p-value = 0.001). These findings demonstrate that video-based educational media significantly improves knowledge regarding sexually transmitted infections among premarital couples. Therefore, the Office of Religious Affairs is recommended to provide video-based educational materials before premarital counseling to improve the knowledge of prospective couples.